2017
DOI: 10.1089/jmf.2016.0167
|View full text |Cite
|
Sign up to set email alerts
|

A Botanical Composition Mitigates Cartilage Degradations and Pain Sensitivity in Osteoarthritis Disease Model

Abstract: Osteoarthritis (OA) is a degenerative joint disease characterized by a progressive articular cartilage degradation manifested with significant functional impairment in consort with signs and symptoms of inflammation, stiffness, and loss of mobility. Current OA management is inadequate due to the lack of nominal therapies proven to be effective in hampering disease progression where symptomatic therapy focused intervention masks the primary etiology leading to irreversible structural damage. In this study, we d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…Furthermore, moracin, a flavonoid from Mores alba root bark protects against IL-1β-induced osteoarthritis by reducing inflammatory factors (TNF-α, IL-6, and COX2) via attenuating the NF-κB pathway [37]. Consistent with previous studies [35][36][37], the present study also demonstrated that MBW attenuated pain and proinflammatory activities in the articular cartilage along with preventing the reduction of serum testosterone concentrations in the testosterone-deficient rats with MIA-induced osteoarthritis. MBW inhibited the BMD loss only in the leg with osteoarthritis, and it was associated with the suppression of osteoarthritis progression.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Furthermore, moracin, a flavonoid from Mores alba root bark protects against IL-1β-induced osteoarthritis by reducing inflammatory factors (TNF-α, IL-6, and COX2) via attenuating the NF-κB pathway [37]. Consistent with previous studies [35][36][37], the present study also demonstrated that MBW attenuated pain and proinflammatory activities in the articular cartilage along with preventing the reduction of serum testosterone concentrations in the testosterone-deficient rats with MIA-induced osteoarthritis. MBW inhibited the BMD loss only in the leg with osteoarthritis, and it was associated with the suppression of osteoarthritis progression.…”
Section: Discussionsupporting
confidence: 91%
“…It is also reported to facilitate weight loss by suppressing appetite and improving dyslipidemia [33,34]. Oral intake of a mixture of Acacia catechu water extract and Morus alba root bark ethanol extract (50 mg/kg BW) has anti-inflammatory (TNF-α and IL-1β), collagenase (MMP-13) inhibitory, and articular cartilage protective activities in MIA-induced arthritis [35,36]. Furthermore, moracin, a flavonoid from Mores alba root bark protects against IL-1β-induced osteoarthritis by reducing inflammatory factors (TNF-α, IL-6, and COX2) via attenuating the NF-κB pathway [37].…”
Section: Discussionmentioning
confidence: 99%
“…Osteoarthritis (OA) is a degenerative joint disease, pathologically characterized by the progressive loss of cartilage, osteophyte formation, subchondral sclerosis, matrix degradation and matrix synthesis imbalance (13). Symptoms of OA include inflammation, stiffness and loss of mobility (1). Currently, OA treatment is challenging due to its multiple etiologies and complex pathological processes (2).…”
Section: Introductionmentioning
confidence: 99%
“…These properties of A. catechu and M. alba were indeed translated into beneficial applications for OA when their standardized composition, UP1306, was tested in vitro and in vivo. To mention a few tests, UP1306 was found to cause (a) suppression of inflammation and pain sensitivity in carrageenan induced rat paw edema model [27], (b) modulation of cyclooxygenase and lipoxygenase activities [27], (c) synergistic inhibition of glycosaminoglycan release ex vivo [27], and (d) increased cartilage sparing activities in monoiodoacetate-induced rat OA model [28]. In a randomized and double-blinded placebo-controlled clinical trial, UP1306 administered at 400 mg/day to arthritic subjects showed significant reduction in urinary C-telopeptides of type II collagen (CTX-II), when compared to placebo after 12 weeks of daily supplementation [29].…”
Section: Introductionmentioning
confidence: 99%